البعد الجيو-استراتيجي الأمنيّ لانفصال السودان ضمن استراتيجية الأمن القومي الأميركي - الرحية رائد رفيق (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تمارس أميركا سياساتها المختلفة في دول العالم انطلاقاً من مصالحها وثوابت أمنها القومي. تحكمها طبقة النخبة الرأسمالية, الذين يمتلكون آليات صناعة القرار فيها, وتهدف الدراسة إلى الوقوف على الدور الذي تؤدّيه واشنطن حول العالم متخذين من انفصال السودان أنموذجاً للسياسات الامريكية المطبقة على المستوى العالمي،و هي صنيعة جماعات المصالح التي تشكل الحكومة الخفية لأميركا والعالم أصلاً, فكانت العمليات الأميركية في القارة الافريقية هادفةً إلى السيطرة على ما تم اكتشافه من مكامن الثروات ، ولم يكن السودان سوى حلقة وصل وعبور وتدخل سريع إلى دول القارة الإفريقية ،ودول الشرق الأوسط بسبب موقعه الجيو-استراتيجي المميز ولغناه بالثروات سواء النفطية ،أو المائية ، أو الغذائية, فكانت عمليات أميركا في السودان التي أدت إلى تجزئته أكبر دليل على أهميته في الاستراتيجية الأمنية الأمريكية, إضافةً للوجود الصيني القوي في القارة السمراء, مما جعل الوجود فيه أمراً في غاية الأهمية فكانت الاستراتيجية الأمريكية الجديدة متمثلة بالتفتيت الطائفي ، والعرقي ،والديني, وقد تجسدت بفصل جنوب السودان عن شماله تحت مسمى الديمقراطية. America exercised its policies in the various countries of the world based on their interests and the fundamentals of national security. Governed by the elite class of capitalism , who have the mechanisms of decision-making in which , and the study aims to identify the role played by Washington around the world putting in the separation of Sudan, a model for U.S. policies applied at the global level , which is originally a creation of interest groups that make up the government’s hidden for America and the world , was the operations American continent meaningful control over what was discovered reservoirs of wealth was not Sudan , only a link , transit and rapid intervention to African countries and countries in the Middle East due to its geo - strategic distinctive and riches riches either oil or water or food , was of America in the Sudan, which hashed led to the biggest proof of its importance in U.S. security strategy in addition to the strong Chinese presence on the continent which made its presence is very important was the new American strategy represented by firing laser sectarian , ethnic and religious has epitomized the separation of southern Sudan from the north under the name of democracy.